Protein C Inhibitor from Human Plasma: Characterization of Native and Cleaved Inhibitor and Demonstration of Inhibitor Complexes with Plasma Kallikrein - Laurell, Martin; Stenflo, Johan (Thrombosis and Haemostasis, 1989)
Protein C inhibitor (PCI) was purified from human plasma using immunoaffinity chromatography and heparin Sepharose chromatography, a method that allowed the purification of active and inactive inhibitor. PCI purified from outdated plasma was inactive and either in complex with plasma kallikrein or proteo-lytically degraded. Sequence analysis of cleaved PCI and of complexes between PCI and activated protein C or urokinase identified the previously recognized inhibitor cleavage site Arg354-Ser355. Two additional cleavage sites were observed in the modified inhibitor i.e. Arg357-Leu358 and Arg362-Leu363 which probably represent secondary cleavage of the inhibitor. Furthermore the sequence analysis of the inhibitor, whether purified from fresh or outdated plasma, revealed that it was microheterogeneous in the NH2-terminus as a result of cleavage by a trypsin like enzyme(s).
Keywords: Protein C; Protein C inhibitor; Plasma kallikrein; Urokinase; Heparin